Oil Shock Impact Upon Energy Companies Investment Portfolios. Trends and Evolutions in the Energy Consumption Sector - Dumiter, Florin Cornel; Turcaș, Florin Marius; Boiţă , Marius (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
In this article, we tackle the complex relationship between a triangle assessment: energy companies, investment portfolios, and the energy consumption sector. The first objective of this paper was to underline several important features of oil price evolution in the pandemic period, with a special focus both on the 2020 and 2022 periods, in order to reveal some aspects of new passengers’ cars registered, and some important energy sources worldwide. Second, it is highlighted several important features of energy-listed companies on the Bucharest Stock Exchange and of oil prices upon different operators. Third, we analyze important aspects of the influence of the crises regarding the energy industry and several important evolutions upon the stock market. The main findings of this study reveal the nexus between oil shock prices, the energy industry, and the stock market with an empirical focus on constructing an optimal investment portfolio’ by considering several consumption sectors. Future research on this topic will encounter consequently comparisons between several business models of different types of sectors.